2009
DOI: 10.1007/s00428-009-0743-9
|View full text |Cite
|
Sign up to set email alerts
|

Extranodular background liver parenchyma of focal nodular hyperplasia: histopathological characteristics

Abstract: Focal nodular hyperplasia (FNH) of the liver is considered to develop as a hyperplastic response to a preexisting vascular abnormality. From the pathogenic point of view, we studied histological alterations in the extranodular background liver tissue of FNH (FNH-bg-liver). We compared ten FNH-bg-livers with ten non-FNH cases (non-FNH-liver) and found small uniform nodule formations with ring-like siderosis in the FNH-bg-livers (4/7, 57%) but not in the non-FNH-livers. Abnormal small arteries not accompanied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Moreover, FNHs are surrounded by liver tissue that is otherwise histologically normal or nearly normal. 1,2 Recently, FNH-like lesions have been reported in cirrhotic livers, 3,4 these nodules are macroscopically, microscopically, and immunohistochemically identical to classic FNH seen in non-cirrhotic livers. 5,6 Recognition of the concept of FNH and FNH-like lesions is very important because these lesions are sometimes difficult to differentiate radiologically from hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, FNHs are surrounded by liver tissue that is otherwise histologically normal or nearly normal. 1,2 Recently, FNH-like lesions have been reported in cirrhotic livers, 3,4 these nodules are macroscopically, microscopically, and immunohistochemically identical to classic FNH seen in non-cirrhotic livers. 5,6 Recognition of the concept of FNH and FNH-like lesions is very important because these lesions are sometimes difficult to differentiate radiologically from hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 98%
“…Focal nodular hyperplasia (FNH) is a well‐circumscribed lesion composed of proliferating benign hepatocytes with a characteristic stellate central fibrous scar. Moreover, FNHs are surrounded by liver tissue that is otherwise histologically normal or nearly normal 1,2 . Recently, FNH‐like lesions have been reported in cirrhotic livers, 3,4 these nodules are macroscopically, microscopically, and immunohistochemically identical to classic FNH seen in non‐cirrhotic livers 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…In one investigation, abnormal small arteries not accompanied by portal tracts were found more often in FNH livers, as were CD34-positive sinusoids around portal tracts. In addition, small uniform nodule formations with ring-like siderosis were noted (Motosugi et al 2009). In a further study, the extranodular liver area in 73 % of FNH cases revealed alterations that were similar to but milder than those in the FNH nodule (Kondo et al 1998).…”
Section: Histopathology Of the Extralesional Livermentioning
confidence: 93%
“…As a result, imaging findings alone per the Liver Imaging Reporting and Data System (LIRADS) criteria may not be reliable in diagnosing HCC in patients with chronic hepatic congestion. Use of hepatobiliary contrast agents that are transported by functioning hepatocytes may help differentiate benign lesions, which more often have a homogenous pattern of retention . In contrast, a mass with a mosaic or heterogenous appearance, necrosis, rapid growth over time, or associated venous tumor thrombus is highly suspicious for HCC (Table ; Fig.…”
Section: Features That Distinguish Benign and Malignant Nodules In Pomentioning
confidence: 99%